Towards becoming critical reflection writers: a case of English language teacher candidates. Issue 6 (2nd November 2018) - Turhan, Burcu; Kirkgoz, Yasemin
ABSTRACT: This study aimed at investigating English language teacher candidates' reflections based on observations of real language teaching. Participants were 49 third-year undergraduate students studying at the English Language Teaching Department of a state university in Turkey. The rationale for selecting third-year students as participants was to describe the characteristics of written critical reflections of teacher candidates before they started practicum experience in their fourth-year of study at university. Participants' critical reflection writings were utilized as data collection tools. The data obtained from reflective writings were analysed based on the Reflection Scale by Bain, Packer and Mills (1999). The analysis of data related to participants' views on the observation and reflection writing process was conducted via inductive content analysis. The qualitative data indicated that English language teacher candidates did not reach a high degree in terms of criticality in their reflections. In addition, they did not tend to become more critical in their reflections over time even though they believed that reflection was beneficial for their professional development.